Division of matrimonial property in Malaysia: the legal historical perspective - Ibrahim, Norliah; Abdul Hak, Nora (Jabatan Sejarah, Universiti Malaya, 2007)
Matrimonial property under the Malaysian family law refers to the property that is jointly acquired by husband and wife during the marriage. Under the present law, in dividing the matrimonial property upon divorce, the court will look at the parties’ contribution either through direct or indirect contribution. The article focuses on the development of the law governing the division of matrimonial property from the historical context. The discussion concentrates on majority of races living in Malaysia i.e., Malay, Chinese and Indian which were previously governed by their customs. It is interesting to see whether customs practised by different races in Malaysia play any role in the development of law concerning the division of the matrimonial property. It will look at how these customs and practices evolved into the present legal provision.